SPECIAL EDUCATION AND ITS ROLE IN THE CONTEMPORARY SCENARIO - Francisco, Deise Juliana; Paraíso, Dayse Isabel Coelho (Seven Editora, 2026)
Considering the challenges of school inclusion for students with disabilities in Brazil, this article aims to understand the role of contemporary Special Education, highlighting barriers and pathways toward equitable inclusion. The objective is to analyze how public policies and inclusive pedagogical practices can contribute to accessible and welcoming school environments. To this end, a literature review was conducted in the CAPES Digital Library of Theses and Dissertations (BDTD), with works defended between 2019 and 2023. A total of 221 studies were identified, of which 17 were selected for meeting criteria of thematic relevance, timeliness, and contribution to the field. Thus, advances are observed, but also persistent challenges in inclusion policies: gaps in teacher training, obstacles in the implementation of inclusive pedagogical practices, and the permanence of attitudinal, structural, and curricular barriers. The data highlight the importance of listening to students, teachers, and families as an indispensable step toward building truly inclusive school environments. The productions also evidence the strategic role of assistive technologies, intersectional approaches, and intersectoral practices as solutions to everyday challenges. This allows us to conclude that, despite significant legal advances, effective school inclusion remains a trajectory under construction, requiring joint efforts between public policies, ongoing teacher training, and school management to ensure access, permanence, and learning for all students in a democratic, equitable, and plural school.